Merger And Acquisition: An Exploratory Search on Survival and Diversification of Newly Built or Small scale Industries in Current Economy - Bohra, MH; Chhabra, I; Kapoor, T; Rathore, D (International Journal of Computer Sciences and Engineering, 2025)
Merger and Acquisition are a common strategy for growing a business. It defines as a consolidation of companies. A merger occurs when two companies combine to form one entity, while an acquisition results from one business taking over and absorbing another. The purpose of this study is to analysis the impact of Merger and Acquisition on Small Scale Industries. Merger and Acquisition are common and in some cases necessary for a business to survive in the current economy. There are several purposes of mergers and acquisitions. But the general purpose of merger and acquisitions are to generate more profit for the newly built companies or small scale companies and also to diversify their operation geographically.